Binding of calcium and strontium by alginates. - Triffitt, J (1968)
SODIUM alginates markedly inhibit the intestinal absorption of strontium in rats1-4 and man5,6 without an appreciable effect on calcium absorption so that they are of interest as possible therapeutic agents in cases of ingestion of strontium-90. Alginic acid is obtained from certain seaweeds and is a polymer of D-mannuronic acid and L-guluronic acid7 joined by 1,4 linkages8. It has been shown that guluronic-rich fractions of alginate are the most effective in reducing strontium absorption in rats in vivo and in vitro4,9. © 1968 Nature Publishing Group.